Modernizing Contracts Across Industries: A Review of Smart Contract Applications and the Evolving Legal Landscape - Bohyer, Kiran; Hayajneh, Thaier (EAI Endorsed Transactions on Scalable Information Systems, 2023)
We provide (1) an overview of various present and future applications of smart contracts across various industries including real estate, finance, and healthcare and (2) an assessment of the efficacy of smart contracts as a means of replacing or supplementing traditional contracts. Disclosed in this paper are (1) present and future applications of smart contracts and potential risks and downsides, and (2) legal considerations when using smart contracts to replace or supplement traditional contracts. Aspects of blockchain technologies can be applied to traditional contracts, in part or in whole, to reduce common challenges associated with contracts. Specifically, smart contracts can be integrated with or replace traditional contracts with the benefit of ensuring reciprocal obligations are enforced and aid in ensuring mutual consent, offer and acceptance, consideration and legal purpose.